Isolation of Vibrio Species from the Gut of Swimming Crabs (Callinectus sp.) and Their Antibiotic Susceptibility - Ashiru, A.W.; Uaboi-Egbeni, P.O.; Odunlade, A.K.; Ashade, O.O.; Oyegoke, T.M.; Idika, C.N. (Pakistan Journal of Nutrition, 2012)
This study was carried out to isolate and identify Vibrio spp in the gut of a swimming crabs (Callinectus sp.) and to determine their susceptibility to antibiotics. The crabs used for the investigation were obtained from Makoko seafoods market, Makoko area of Lagos state. The presence of Vibrio spp in crabs was established using a selective media. Thiosulphate Citrate Bile Salt Agar (TCBS) agar. The following Vibrio sp.; Vibrio parahaemolyticus, Vibrio cholerae and Vibrio mimicus were isolated and identified from the gut of the crabs investigated based on the cultural, morphological and Biochemical characteristics. V. parahaemolyticus has the highest cfu/ml of 4.4 x 104. The antimicrobial susceptibility of the isolates were also determined where Ciprofloxacin (10 μg) and Perfloxacin (5 μg) was the most susceptible with zone of inhibition of 26 mm while they were resistant mostly to Ceftriazone (30 μg) and Gentamycin (10 μg). The presence of Vibrio sp in crabs which are potential human pathogens indicates the need for public enlightenment, campaign and general education on proper handling and thorough cooking of crabs is important in reducing the outbreak of the disease. However, antimicrobial susceptibility test should be carried out before treatment related to Vibrio sp.